Play in two languages. Language alternation and code-switching in role-play in North Sámi and Norwegian - Kleemann, Carola Babette (Nordlyd, 2013)
This article analyses how children in a Sámi kindergarten use their languages, North Sámi and Norwegian, in everyday life. My focus is on role-play in periods of free play in a kindergarten where children speak both North Sámi and Norwegian. Role-play is a bilingual context in that one sequence of play most often uses elements from both languages. Role-play as a situation is suitable for studying language alternation and code-switching because it is an in-group driven activity. The language alternation and code-switching which appears in role-play situations is discussed in light of theories advocating dividing code and language, viewing language choice as one of a cluster of codes used in role-play. I argue the children observed for this study have layers of codes to use. I discuss the language codes North Sámi, Norwegian and bilingual, which the children use in the role-play setting; the main codes used are directory utterances, role utterances, magical utterances and out-of-play-utterances.